Desain Sistem Berorientasi Objek Pada Retail Minimarket Surya Mart - Sunardi Sunardi; Abdul Fadlil; Tresna Yudha Prawira (STIKOM Tunas Bangsa Pematangsiantar, 2019)
The process of a minimarket retail business needs a system infrastructure so that the management process is easier to do and business processes can run more effectively. In this research, a system design process is carried out to give an overview of the business units at the Surya Mart minimarket retail, to create a system design object-oriented system analysis by making a UML diagram (unified modeling language) including making use case diagrams, activity diagrams, sequence diagram, and class diagram. From the results of the analysis, the results of this study obtain the results of a design or system design in the form of user interface design, database structure and structured query language to become a reference in the development process of the business to become a product application for the Surya Mart retail minimarket business process.